GRADE equity guidelines 3: considering health equity in GRADE guideline development: rating the certainty of synthesized evidence - Vivian A. Welch (2018)
© 2017 The Authors Objectives The aim of this paper is to describe a conceptual framework for how to consider health equity in the Grading Recommendations Assessment and Development Evidence (GRADE) guideline development process. Study Design and Setting Consensus-based guidance developed by the GRADE working group members and other methodologists. Results We developed consensus-based guidance to help address health equity when rating the certainty of synthesized evidence (i.e., quality of evidence). When health inequity is determined to be a concern by stakeholders, we propose five methods for explicitly assessing health equity: (1) include health equity as an outcome; (2) consider patient-important outcomes relevant to health equity; (3) assess differences in the relative effect size of the treatment; (4) assess differences in baseline risk and the differing impacts on absolute effects; and (5) assess indirectness of evidence to disadvantaged populations and/or settings. Conclusion The most important priority for research on health inequity and guidelines is to identify and document examples where health equity has been considered explicitly in guidelines. Although there is a weak scientific evidence base for assessing health equity, this should not discourage the explicit consideration of how guidelines and recommendations affect the most vulnerable members of society.